Compras públicas compartilhadas: análise da eficiência do processo licitatório centralizado da Guarnição Militar de Santa Maria - Barreiro, Miguel Esposito (2019)
Public organizations are fundamental to society, which in a constant process of transformation, demands from these institutions the need to adapt their mission to each new challenge. The Brazilian Army (EB), like any other public organization, faced with the shortage of public resources, seeks to improve the management of the public good in order to have a more efficient, efficacious and effective ground force. In this sense, the EB implemented in Santa Maria / RS a pilot program for administrative rationalization and one of the outcomes of this Program is the Santa Maria Garrison Bidding Section (SL Gu SM), which now acts as a facilitator for the 21 Military Organizations (OM) of that city, giving options for its budget execution, potentializing the benefits of shared and large-scale purchase. Thus, this research is a case study that aims to analyze SL Gu SM's shared purchasing processes, in the Electronic Auction mode, and identify if they are achieving the principles of efficiency. For the purposes of this research, it was considered the context of efficiency regarding speed; the economy; the quantity of items purchased and finally the specificity. Regarding the approach to the problem, the study used mixed methods (qualitative and quantitative). The quantitative analysis was based on secondary data available on the portal www.comprasnet.gov.br concerning electronic trading sessions, price registration system from 2016 and 2017. Relating to the qualitative approach, semi-structured interviews were conducted with the main actors involved. After the data collection, information was compared using the triangulation of sources: document analysis, interviews and participant observer. It was noted the need to reorganize the Section's organizational structure by presenting a new organization chart, aiming to facilitate the flow of the bidding process by aligning leadership, strategy and control. It was observed that the biggest bottleneck in SL Gu SM's execution process is the large number of items that are part of the standard list, even that the vast majority are not purchased and / or contracted; coupled with the lack of information technology systems, applied to logistics, to integrate the various sectors of the organization both internally and externally; the lack of planning on the part of the participating organizations, which is a prime factor to achieve greater process efficiency, as well as the training of managers, crier and support staff. Finally, improvement actions based on leadership, strategy and control measures were presented, aiming at minimizing the problems related to external factors, the lack of unification of procedures, the time of the processes, avoiding superfluous items and the same object, thereby eliminating rework and thus improve procurement planning for greater efficiency of the procurement.